Post-COVID central hypersomnia, a treatable trait in long COVID: 4 case reports - Morelli-Zaher, Clémence; Vremaroiu-Coman, Andrea; Coquoz, Nicolas; Genecand, Léon; Altarelli, Marco; Binkova, Alzbeta; Frésard, Isabelle; Bridevaux, Pierre-Olivier; Gex, Grégoire (Frontiers in Neurology, 2024)
Fatigue is the most commonly reported post-COVID symptom. A minority of patients also report excessive daytime sleepiness, which could be a target for treatment.Methods: Among 530 patients with a post-COVID condition, those with excessive daytime sleepiness were assessed for central hypersomnia.Results: Four cases of central hypersomnia were identified according to the International Classification of Sleep Disorders Third Edition criteria (three idiopathic hypersomnia and one type II narcolepsy). We report here their clinical history, sleep examination data and treatment, with a favorable response to psychostimulants in three cases and spontaneous resolution in one case.We highlight that it is important to identify these cases as central hypersomnia may be a treatable trait of a post-COVID condition.1.